Diversidade e identificação do potencial antagonista de fungos endofíticos cultiváveis de variedades de Capsicum chinense Jacquin - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The microorganisms that inhabit the interior of plants, known as endophytes, have been explored for several applications due to their production of important chemical compounds such as enzymes, alkaloids, antibiotics, anticancer and other different metabolites. Capsicum chinense is a species of pepper found in all regions of Brazil and which presents an expressive variability of fruits in different shapes and colors, two of these varieties are quite appreciated for consumption in the North region, a territory that also stands out as a center of diversity in pepper species C. chinense, the typical varieties of this region are murupi and scented peppers, objects of interest in this study, as they are condiments widely used in local cuisine. The objective of this work was the isolation, identification and evaluation of the antagonistic potential of endophytic fungi obtained from Capsicum chinense. The fruits were collected in Presidente Figueiredo, a municipality located in the Metropolitan Region of Manaus. The isolates were obtained by the technique of fragmentation of plant tissues, which were plated in Potato Dextrose Agar (PDA), at 28 ºC, and after obtaining purified colonies the fungi were evaluated for their antibacterial action against Staphylococcus aures strains, Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa and against phytopathogens of the genus Colletotrichum spp, causing anthracnose in guaranazeiro samples. To obtain the extracts, the isolates were grown in PDA medium, mycelial fragments were crushed and transferred to Erlenmayers of 500 mL containing 300 mL of ethyl acetate. The disk diffusion assay was performed to assess antibacterial activity and the antifungal activities were analyzed in direct confrontation tests. 157 endophytic fungi were isolated from the two varieties of peppers, 15.6% of the fragments of the endocarp and 2% of seeds, due to the number of isolated fungi, they were initially grouped into six groups based on their morphological characteristics. Different endophytes exhibited different levels of bioactivity against the pathogens used in this study. In the antibacterial activity test, four isolates, where two of them were identified as Diaporthe sp. and Diaporthe phaseolorum, showed to be active against Staphylococcus aureus. In the direct confrontation between endophytic fungi and pathogens, three endophytes belonging to the species Neoscytalidium dimidiatum and a strain of Diaporthe phaseolorum were effective in suppressing the phytopathogen (GP131) of the guaraná culture with an antagonism rate of 80%, being the highest rate of antagonism was the endophyte Neoscytalidium dimidiatum that inhibited the two phytopathogens (GP131 and ISO6 / R4) analyzed in this study. In the evaluation of fungal extracts against phytopathogens, isolates from Diaporthe sp. with active compounds that inhibited the development of Colletrotrichum cf. gloeosporioides and Colletotrichum siamense.
Keywords: Microrganismos endófitos; Bioatividade; Anticancerígenos; Fitopatógenos; Atividade antibacteriana; CIÊNCIAS BIOLÓGICAS; Microbiota; Fungos endofíticos; Colletotrichum; Antagonismo; Compostos ativos; Termoestabilidade